Estimation of Underdamped Overshoot in Second-Order Control Systems - Mishra, Rakesh; Upadhyay, J.P; Gupta, Surekha (International Journal of Computer Sciences and Engineering, 2025)
The paper investigates the problem of overshoot estimation decreasing for underdamped second-order control systems. A new technique to control the overshoot is proposed, which is based on Posicast control and proportional integral and derivative (PID) control, which performs switching between two controllers. The aim is to use open-loop feedforward control to increase tracking performance and PID control to deal with disturbance rejection. It has been shown that the proposed control scheme can have some advantages over the classical approaches without switching capabilities